2005
DOI: 10.1079/pns2005432
|View full text |Cite
|
Sign up to set email alerts
|

Hospital mealtimes: action research for change?

Abstract: Poor nutritional care within the hospital setting continues despite decades of work chronicling and measuring the problems. To address the problem changes in practice have been attempted to improve the patients' experience of mealtimes. In order to implement patient-centred mealtimes for older patients by changing the focus from institutional convenience to one that focuses on the requirements of the patients, an action research approach has been used that focuses on action and change, and thus appears to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 31 publications
1
40
0
5
Order By: Relevance
“…This gave the insight to the fact that the care personnel also needed the information that was provided in the information letters. This knowledge is consistent with results from other studies showing that food preparation and distribution related tasks had a low status and that the personnel who frequently had the responsibility for this service often had a low level of education [1,37] . Even though the 1992 reform was introduced 20 years ago, the municipalities have still not yet resolved the problems of ensuring that those personnel who are involved in the municipal FD service have the correct competence.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…This gave the insight to the fact that the care personnel also needed the information that was provided in the information letters. This knowledge is consistent with results from other studies showing that food preparation and distribution related tasks had a low status and that the personnel who frequently had the responsibility for this service often had a low level of education [1,37] . Even though the 1992 reform was introduced 20 years ago, the municipalities have still not yet resolved the problems of ensuring that those personnel who are involved in the municipal FD service have the correct competence.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…Limited verbal interaction and lack of spontaneous interactions between older people and staff associated with hydration have been reported elsewhere (Ullrich and McCutcheon, 2008). The social aspects of mealtimes in hospital have similarly been described as impoverished (Dickinson et al, 2005). Removing this important dimension contributed to a diminution in the quality of the drinking experience for older people.…”
Section: Discussionmentioning
confidence: 99%
“…While nurses may view the nutritional care of patients as an important aspect of their job, increased time pressures and competing tasks may mean that they are not able to prioritise feeding above other duties, such as the distribution of medicines at meal times (Kowanko et al 1999;Dickinson, et al 2005). Most research in this area has reported common themes of time restraints and staff shortages.…”
Section: Introductionmentioning
confidence: 99%
“…Most research in this area has reported common themes of time restraints and staff shortages. Attention by nurses and other staff to patient meal times can have a positive affect on patient eating habits (Dickinson et al 2005;Kayser-Jones & Schell 1997a;Chang et al 2003).…”
Section: Introductionmentioning
confidence: 99%